Preparation and luminescence properties of YAG:Ce phosphor for white LED application via a vacuum sintering method. Issue 7 (14th April 2014) - Shi, Hongling; Chen, Jian; Huang, Jiquan; Hu, Qianqian; Deng, Zhonghua; Cao, Yongge; Yuan, Xuanyi
<x xml:space="preserve">Abstract</x> YAG:Ce phosphors are synthesized by the vacuum sintering method, and their crystal structure, luminescence properties, and X‐ray photoelectron spectroscopy are discussed. The synthesized temperature of pure YAG phase is reduced by vacuum sintering. As‐synthesized YAG:Ce phosphors show a smaller average size of about 1 μm due to the fine starting materials, low sintering temperature, and the absence of flux. It is found that samples synthesized by the vacuum sintering method show stronger emission intensity and higher optimized Ce3+‐doping concentration. In addition, white light‐emitting diodes (LEDs) with improved color‐rendering properties are obtained by using modified Pr3+‐doped YAG:Ce phosphors.